WHY, WHEN WE ARE DEEMED TO BE CARERS, ARE WE SO MEAN TO OUR COLLEAGUES? - Fudge, Lesley (Operating Room Nurses Association of Canada Journal, 2006)
The author discusses horizontal and vertical violence as they have existed in nursing for many years but are only recently beginning to be discussed and dealt with. Horizontal violence – across peer groups and similar levels of staff Vertical violence – from senior to junior colleagues usually downwards but possible upwards The article will consider some of the issues from examples around the world and how they impact on perioperative nurses.